COMPARATIVE EFFICACY OF ISOSORBIDE MONONITRATE AND MISOPROSTOL VERSUS MISOPROSTOL ALONE FOR CERVICAL RIPENING AND INDUCTION OF LABOR: A RANDOMIZED DOUBLE-BLIND STUDY - SHARMA, MOLLY; BHARDWAJ, DEEPAK (International Journal of Current Pharmaceutical Research, 2024)
Objective: Induction of labor is a common obstetric procedure aimed at initiating uterine contractions before the spontaneous onset of labor, essential for achieving vaginal delivery. Misoprostol, a synthetic prostaglandin E1 analog, is widely used for cervical ripening and labor induction but is associated with potential side effects. Isosorbide mononitrate (ISMN), a nitric oxide donor, has emerged as a potential adjunct to enhance cervical ripening. This randomized, double-blind study evaluates the comparative efficacy of ISMN combined with misoprostol versus misoprostol alone for cervical ripening and labor induction in term pregnancies. Methods: This study was conducted at the Department of Obstetrics and Gynecology, Dr. R. P. G. M. C. Kangra, Himachal Pradesh, from July 2019 to June 2020. A total of 100 patients meeting the inclusion criteria were randomized into two groups: Group 1 received ISMN 40 mg and misoprostol 25 mcg, while Group 2 received misoprostol 25 mcg and a placebo. The primary outcome was the induction to active phase interval. Secondary outcomes included mode of delivery, maternal and neonatal outcomes, and side effects. Statistical analysis was performed using Chi-Square and unpaired t-tests, with a p-value<0.05 considered significant. Results: Group 1 (ISMN+misoprostol) showed a significantly shorter induction to active phase interval (11.85±3.24 h) compared to Group 2 (misoprostol alone) (19.82±3.7 h, p=0.004). The mode of delivery did not significantly differ between groups, with similar rates of vaginal delivery and cesarean sections. Neonatal outcomes, including birth weight and APGAR scores, were comparable between the groups. Maternal complications were not significantly different, with no increased incidence of hyperstimulation or postpartum hemorrhage in group 1. Conclusion: The combination of ISMN with misoprostol is more effective in reducing the induction to active phase interval compared to misoprostol alone without increasing adverse maternal or neonatal outcomes. This combination therapy could represent a significant advancement in the management of labor induction.